Four new species of Mileewini leafhoppers (Hemiptera: Cicadellidae: Mileewinae) from China, with a checklist to Chinese species - He, Hong-Li; Yan, Bin; Yang, Mao-Fa; Webb, M.d. (Zootaxa, 2021)
Four new species of Mileewini, Mileewa clavata He & Yang, sp. nov., Mileewa rubricosta He & Yang, sp. nov., Mileewa quinquemaculata He & Yang, sp. nov. and Ujna liboensis He & Yang, sp. nov., are described and illustrated. A checklist of all Chinese Mileewini is provided.